Pengaruh Kualitas Layanan E-Form terhadap Tingkat Kepuasan Nasabah pada PT Bank Syariah Indonesia Kantor Cabang Mataram Pejanggik 1: Studi pada Mahasiswa Perbankan Syariah 2020/2021 UIN Mataram - Faizah, Mar’atun (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research is a descriptive quantitative study which aims to examine the effect of e-form service quality on the level of customer satisfaction. The method used in this research is a quantitative method. The research population used 106 Islamic Banking students from the 2020/2021 Faculty of Economics and Islamic Business, UIN Mataram and the sample used was 85 people. Data collection techniques in research are observation, documentation and questionnaires. The data in this research was obtained from the results of distributing questionnaires to a sample of 85 people, all of whom were 2020/2021 Islamic Banking students at the Faculty of Islamic Economics and Business, UIN Mataram. Based on the results of the hypothesis test that has been carried out, the research results show that the electronic service quality variable has a significant effect as proven by the results of data analysis, namely, tcount 9.462 > ttable 1.992, which means that there is an influence of electronic service quality on customer satisfaction. And, based on the results of partial analysis in simple linear regression, it can be seen that the significance value (Sig.) of 0.000 is smaller than <0.05 and it can be concluded that H0 is rejected and H1 is accepted, which means that there is an influence of electronic services on the level of customer satisfaction. And the results of the path analysis showed that the influence of electronic service quality had a positive and significant effect on customer satisfaction with a coefficient of 0.519. And it can be concluded from the data obtained that the quality of electronic services has a significant and positive influence on the level of customer satisfaction.